Disinfection efficiency for Escherichia Coli inactivation in water using low frequency ultrasonification effect of temperature, power and volume change on inactivation - Biel, Luisa C. B. (Philippine Engineering Journal)
The present study explored the application of 20-kHz ultrasonic processor for water disinfection in conjunction with the thermal effect of the process. The experiments were divided into three stages : variable temperature, variable amplitude and variable volume. Temperature affects the ultrasonic treatment significantly by reducing the treatment time. For controlled temperature experiment, 5 log (base 10) reduction was achieved after 30 minutes of treatment, as compared to the 10 minutes of contact time for experiment without temperature control. The disinfection efficiency of E. coli increased with increase in the power input, through change in amplitude, from 0.140 log kill.min at the lowest power (122 W/L) to 0.799 log kill/min at the highest power (310 W/L). Power is directly proportional to temperature; wherein, maximum temperature of 61 degree celcius was attained utilizing power input of 310 W/L. As for the effective volume of the sample, increasing the volume reduces the concentration of the energy being dissipated in the sample. After 30 minutes of treatment the maximum percent inactivation for 500 mL and 1000 mL are 98.30 percent and 97.35 percent respectively. Overall, there exists a synergy between ultrasound and heat, such that ultrasonic treatment increased the vulnerability of E. coli to heat.